PENGARUH PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP MARKET VALUE ADDED DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan yang termasuk dalam peringkat CGPI 2009-2011) - Hayu Wikan Kinasih (MEDIA, 2013)
Corporate Social Responsibility or known as CSR, is a corporate activity to response what the the stakeholders have done to the company. Company’s hope that the stakeholder will give a positive responses  through CSR that showed in company’s financial performance. According to Stern Steward, Market Value Added (MVA) is the best tools to measure company’s financial performance. MVA shows how much values does the company created. The aim of this research is to test if  Good Corporate Governance (GCG) would increase the relationship between CSR and MVA. The research sample was Governance Perception Indeks (CGPI) participants held by IICG (The Indonesian Institute for Corporate Governance)  from 2009  to 2011. Use some criteria, there are 40 companies choosen as a sample. From the research that the writer do through the model that use MRA (Market Regression Analysis), GCG that measure with CGPI score, was not  provided as a moderating variable. The significance level of the interaction variable (CSRI * CGPI) is >0,05 that is 0,569.  Adjusted R2 as determinating variable shows 11% which means that CSRI, CGPI and lnCSR_CGPI variable could explain dependent variable lnMVA with the total 11%, and 89% remaining was explained by another variable outside the model.